2001
DOI: 10.1088/0953-8984/13/28/306
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the Fermi golden rule and the possibility of low-field runaway transport in nitrides

Abstract: In order to justify applicability of the standard approach of perturbation theory for the description of transport phenomena in wide-band polar semiconductors with strong electron-phonon interactions, we have compared dependences of energy losses to the lattice on the electron drift velocity obtained for different materials in the frameworks of (a) a perturbative approach based on calculation of the scattering rates from Fermi's golden rule and (b) a non-perturbative approach based on the path-integral formali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 16 publications
1
20
1
Order By: Relevance
“…Since plasma oscillations mix the symmetry properties of E 1 and A 1 modes and their LO/TO character, resulting in both Raman and IR active vibrations as experimentally evidenced [18,24]. With these in mind we are right in believ- ing that the third branch, 3 ω may also be both a Raman and IR active vibration. All these modes are plotted in Fig.…”
Section: Phonons In Bulk Zno Crystalsmentioning
confidence: 76%
See 3 more Smart Citations
“…Since plasma oscillations mix the symmetry properties of E 1 and A 1 modes and their LO/TO character, resulting in both Raman and IR active vibrations as experimentally evidenced [18,24]. With these in mind we are right in believ- ing that the third branch, 3 ω may also be both a Raman and IR active vibration. All these modes are plotted in Fig.…”
Section: Phonons In Bulk Zno Crystalsmentioning
confidence: 76%
“…The other three are the plasmon-optical phonon coupled modes dispersion laws. Additionally to 1 ω and 2 ω modes (often noted , ω ω + -in the literature) [17][18][19]22], due to uniaxial anisotropy of the system, a third branch, 3 ω appears. It lies in the ( ||,TO ,TO , ω ω^) frequency domain.…”
Section: Phonons In Bulk Zno Crystalsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of intermediate electron-phonon interaction strength some care is needed. In the case of wurtzite GaN and AlN it was found that the usual perturbative treatment (FermiÕs Golden Rule) can be applied [34] in spite of the relatively strong electron-phonon coupling in these materials. This conclusion was reached by comparing the results obtained in the framework of a perturbative approach based on the calculation of scattering rates by the FermiÕs Golden Rule and those obtained with a nonperturbative approach based on the path-integral formalism of Thornber and Feynman [35].…”
Section: Scattering Rates: Results and Discussionmentioning
confidence: 99%